Effects of Multiple Mycotoxins and a Hydrated Sodium Calcium Aluminosilicate in Poultry - Watts, C.M.; Chen, Y.C.; Ledoux, D.R.; Broomhead, J.N.; Bermudez, A.J.; Rottinghaus, G.E. (International Journal of Poultry Science, 2003)
Effects of feeding a combination of mycotoxins at naturally occurring levels in broiler chicks and turkey poults were evaluated. The efficacy of a hydrated sodium calcium aluminosilicate (HSCAS) to ameliorate the effects of the combination of mycotoxins was also determined. Day-old chicks and poults were randomly assigned to each of four dietary treatments for 21 days. A 2 x 2 factorial arrangement was used with treatments containing either no mycotoxins or multiple mycotoxins (MM) with 0 or 1% HSCAS. The MM consisted of 1 mg deoxynivalenol, 5 mg moniliformin, 5 mg fumonisin B1, 100 μg aflatoxin B1, 1 mg zearalenone, and 0.5 mg ochratoxin A per kg diet. In experiment 1, feed intake and BW gain were decreased (P < 0.05) in chicks fed MM. Relative heart and gizzard weights were higher (P < 0.05) in chicks fed diets containing MM. Serum albumin levels were decreased (P < 0.05) in chicks fed diets containing MM and HSCAS. In experiment 2, performance of poults was not affected (P > 0.05) by dietary treatments. Relative spleen weights, serum albumin, protein, globulin, and calcium levels were decreased (P < 0.05) in poults fed MM. Mean cell volume was decreased (P < 0.05) in poults fed diets containing HSCAS. Data indicate that a combination of low levels of mycotoxins decreased chick performance and altered several hematological and serum biochemical values in poults. Addition of HSCAS to diets containing MM did not prevent the negative effects observed in chicks and poults.